Contribution of traditional Chinese medicine combined with conventional western medicine treatment for the novel coronavirus disease (COVID‐19), current evidence with systematic review and meta‐analysis. (13th July 2021) - Jiang, Fei; Xu, Nana; Zhou, Yanxi; Song, Jinxing; Liu, Jinjuan; Zhu, Hong; Jiang, Jihong; Xu, Yonghong; Li, Rongpeng
Abstract : This study provides current evidence for efficacy and safety of treating COVID‐19 with combined traditional Chinese medicine (TCM) and conventional western medicine (CWM). Six databases were searched from January 1 to December 31, 2020. Randomized controlled trials (RCTs), case–control studies (CCTs), and cohort studies on TCM or TCM combined with CWM treatment for COVID‐19 were included. The quality of included RCTs was assessed by Cochrane risk of bias tool, and the Newcastle‐Ottawa Scale (NOS) was used to assess the quality of cohort studies and CCTs. Review Manager 5.4 software was used to perform meta‐analysis. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. A total of 35 studies (3, 808 patients) composing 19 RCTs and 16 observational studies were included. The results of meta‐analysis revealed that comparing with CWM alone, integrated TCM and CWM had significant improvement in total effective rate, improvement rate of chest CT, the rate of disease progression, as well as improvement of fever, fatigue and cough. The overall quality of evidence was very low to moderate. In conclusion, TCM combined with CWM was a potential treatment option for increasing clinical effective rate, improving the clinical symptoms, and preventing disease progression in COVID‐19 patients. High‐quality clinical trials are required in the further.